Validation of MODIS data for localized spatio-temporal evapotranspiration mapping - Hashim, Mazlan (2013)
Advancement in satellite remote sensing sensors allow evapo-transpiration (ET) from land surfaces to be derived from selected reflectance and emmitance in visible and thermal infrared wavelengths, such as using Moderate Solution Imaging Spectrometer (MODIS). In this paper, we report the validation of recent MODIS-generated higher-order global terrestrial ET product 16A2. The main focus of this paper is to devise the follow-up calibration for the localised region covering the entire Malaysia peninsular. The validation is carried out locally by dividing the study area into 3 distinct climatological regions based on the influence to monsoons, and using multi-temporal MODIS data acquired in 2000-2009. The result, evidently show the local effects still inherit in the MODIS 16A2 products; with varying R2 within the 3 local climatological regions established (Northwest = 0.49 South = 0.47, and Southwest = 0.52; all with P < 0.001). The accuracy each region validated is within + RMSE 43mm for monthly ET. With P value in acceptable range, the correction is useable for further usage.